Spiritualitas dan Kesadaran Sosial dalam Tarekat Naqsyabandiyah: Studi Transformasi Hubungan Sosial di Yayasan Kiblatul Amin Dua - Alya Izza Irsalina; Moh. Yasir Alimi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This article aims to explain the integration process of Naqshbandi Sufi teachings with the concept of Level of Consciousness developed by David R. Hawkins, and its impact on the transformation of social relationships at Yayasan Kiblatul Amin Dua (YKAD). This research employs a qualitative method with a phenomenological approach to explore the experiences of community members in applying consciousness values in their daily lives. Data were collected through in-depth interviews, participant observation, and documentation. The Level of Consciousness theory explains that human consciousness evolves through certain levels, ranging from lower states such as shame, anger, and pride to higher states such as love, peace, and enlightenment. The findings reveal that prior to the integration of the consciousness concept, social relations within YKAD were exclusive, closed, and primarily focused on vertical relationships with God. However, after implementing the LoC framework in spiritual learning, members experienced increased consciousness, evidenced by greater empathy, open communication, and active participation in social activities. This transformation not only strengthened internal community cohesion but also fostered more harmonious family relationships and improved social acceptance from the surrounding society. The study highlights the importance of self-consciousness as a bridge between spirituality and harmonious social life.